NODULASI RHIZOBIUM DAN PERTUMBUHAN BIBIT SENGON (Paraserianthes falcataria) YANG DIINOKULASI FUNGI MIKORIZA PADA CEKAMAN LUMPUR SIDOARJO - Sutarman, Sutarman (JURNAL AGROTROPIKA, 2020)
This study aims to find out: (i) the influence of mycorrhizal fungi and the percentage of Sidoarjo mud on Rhizobium’s nodulation and sengon seedling growth, and (ii) percentage mud that provide the same relative response of seed growth compared with no mud. The factorial experiment was repeated 3 times with the first factor: the percentage of mud (0%, 10%, 20%, and 30%) and the second factor: mycorrhizal fungi (without and with mycorrhiza). Sidoarjo mud and mycorrhizal fungi affect the intensity root nodules, growth of seedlings, fresh weight and dry weight of seedlings. The percentage of mud to 10% relativey gave a response of intensity of root nodules, growth, and intensity of mycorrhizal infection did not differ with ‘without mud’ and better than the percentage of sludge 20% and 30%. Key words: Sidoarjo mud, Paraserianthes seedling, mycorrhiza, Rhizobium nodulation